Upaya Bhabinkamtibam Dalam Mengurangi Tindak Pidana Curanmor - Michael Batara (Police Studies Review, 2020)
This research is motivated by the high level of success of the Bhabinkamtibmas unit in reducing the crime of motorized theft by counseling the public in the Majalengka Police jurisdiction. This research is discussed by using the concept and theory as a knife of analysis, which uses the concept of counseling, crime prevention, and the concept of Bhabinkamtibmas. This research was conducted with a qualitative approach, using descriptive research methods. Data collection techniques by interview, observation, and document review. The results of the study found that the conditions in the Majalengka Police Binmas Unit were still minimal, this can be seen from the number of HR needs and the availability of HR in each unit and the Sector Police that were still inadequate. This has an impact on the performance of the Police Force. The Guidance and Counseling in the Majalengka Regency was conducted through a lecture approach and visits to crowded places were carried out to facilitate the dissemination of messages. The factors that influence the efforts of binmas units to prevent acts of violation consists of two factors, namely internal factors and external factors. Included in internal factors include the lack of personnel of Majalengka Regional Police Binmas Unit and facilities and infrastructures that can support the results or educational outcomes. While external factors consist of the condition of the Majalengka area which inhibits the affordability of the Bhabinkamtibmas in reaching an area that is difficult to access, as well as minimal public awareness in absorbing kamtibmas messages which impacts on the lack of public awareness of environmental security and a sense of sensitivity to the law. The form of preventive measures undertaken by the Binmas Unit is to carry out counseling. The material presented in general only addresses Kamtibmas. Not explain in detail related to criminal acts Curanmor.